PDCT-12. CLINICAL EFFICACY OF ONC201 IN THALAMIC H3 K27M-MUTANT GLIOMA. (11th November 2019) - Rahman Kawakibi, Abed; Gardner, Sharon; Chi, Andrew; Kurz, Sylvia; Wen, Patrick; Arrillaga-Romany, Isabel; Batchelor, Tracy; Butowski, Nicholas; Sumrall, Ashley; Shonka, Nicole; Harrison, Rebecca; DeGroot, John; et al.
Abstract: ONC201, the first bitopic DRD2 antagonist for clinical oncology, has shown efficacy in H3 K27M-mutant glioma. We performed an integrated preclinical and clinical analysis of ONC201 in thalamic H3 K27M-mutant glioma. ONC201 was effective in mouse intra-uterine electroporation (IUE)-generated H3 K27M-mutant gliomas, with an in vitro IC50 of 500 nM and 50% prolongation of median survival in vivo (p=0.02, n=14). Elevated DRD2 expression was found in the thalamus of non-malignant brain tissue, leading to the hypothesis that thalamic tumors may be a particularly ONC201-sensitive sub-group. We analyzed thalamic H3 K27M-mutant glioma patients treated with ONC201 as of the 05/22/2019 cutoff date, which included patients who had recurrent disease prior to initiating ONC201 (n=20; 15–73 years old) and post-radiation non-recurrent patients (n=11; 5–19 years old). As of 5/22/2019, 10 of 20 recurrent patients and 9 of 11 non-recurrent patients remain on-treatment. Median PFS has not been reached for either cohort: median follow-up of 2.2 months (range: 0.6–37.9) for recurrent patients and 10.6 months (range: 4.3–20.5) from diagnosis for non-recurrent patients. Best response so far by RANO includes 1 CR, 2 PR, 7 SD, 9 PD, 1 NE for recurrent patients and 1 PR, 7 SD, 3 PD for non-recurrent patients. Additionally, 3 recurrent (-66%, -47%, -34%) and 2 non-recurrent (-40%, -10%) patients experienced regressions but are not yet confirmed PRs. For recurrent patients, median onset of response is 3.5 months (range: 2.2–3.8) and median duration of response has not been reached with a median follow-up of 12.5 months (range: 8.1–32.8). Preliminary analyses demonstrated a strong correlation of cell-free tumor DNA in plasma and CSF with MRI response. In summary, ONC201 demonstrates promising clinical efficacy in thalamic H3 K27M-mutant glioma patients, regardless of age. Micro-environmental DRD2 expression may enhance the overall ONC201 response and extend its therapeutic utility beyond H3 K27M-mutant glioma.